Role of Consanguinity on Pediatric Haematological and Pulmonary Health: A Comparative Study at a Tertiary Care Teaching Hospital, Guntur, Andhra Pradesh - Chintaluri, Sai Pranathi Sravani; Chinnam, Sreeja; Katta, Santosh Kumar; Yanamadala, Pavan Kumar; Kambam, Srinivasa Rao; Banala, Ramesh Kumar; Nadendla, Rama Rao (Asian Journal of Biological and Life Sciences)
Background: Consanguineous marriage, characterised as a union between individuals who are second cousins or closer, continues to be culturally significant in certain regions of India and is linked to heightened homozygosity and an elevated risk of autosomal recessive disorders. Grasping its effects on child health is crucial for informing preventive measures. Objectives: The objective is to evaluate how parental consanguinity influences the occurrence of haematological and pulmonary disorders in children receiving care at a tertiary teaching hospital. Materials and Methods: A cross-sectional observational study was carried out involving 209 children aged between 0 and 18 years. Participants were divided into two groups: consanguineous and non-consanguineous, according to their parental relationship history. Information regarding demographic characteristics, clinical findings, and confirmed diagnoses was gathered through a structured proforma. Statistical analysis was conducted using SPSS version 26.0, with a significance level set at a p-value of less than 0.05. Results: Haematological disorders occurred with greater frequency (86.1%) compared to pulmonary disorders (13.9%). Notable associations were identified between consanguinity and thalassemia (p=0.03), sickle cell anaemia (p=0.01), and asthma (p=0.003). In contrast, haemophilia did not demonstrate a significant difference (p=0.09). A male predominance was observed in X-linked disorders, whereas autosomal conditions exhibited an even distribution. Conclusion: Parental consanguinity significantly adds to the prevalence of pediatric haematological disorders and may affect the incidence of multifactorial pulmonary diseases. Enhanced genetic counselling, community-oriented screening, and awareness programs are essential to mitigate preventable genetic morbidity in high-risk groups.
Keywords: Asthma; Consanguinity; Genetic Counselling; Pediatric Health; Sickle Cell Anaemia; Thalassemia.